2015
DOI: 10.1080/13825585.2015.1111291
|View full text |Cite
|
Sign up to set email alerts
|

How older adults use cognition in sentence-final word recognition

Abstract: This study examined the effects of executive control and working memory on older adults' sentence-final word recognition. The question we addressed was the importance of executive functions to this process and how it is modulated by the predictability of the speech material. To this end, we tested 173 neurologically intact adult native English speakers aged 55-84 years. Participants were given a sentence-final word recognition test in which sentential context was manipulated and sentences were presented in dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 105 publications
1
14
0
Order By: Relevance
“…The aspects in question are uncertain. Perhaps, age represents cognitive decline different from working memory capacity, such as processing speed ( Salthouse, 1996 ) or attention ( Craik & Byrd, 1982 ), both of which might affect performance in demanding speech-in-noise situations (e.g., Cahana-Amitay et al., 2016 ; Oberfeld & Klöckner-Nowotny, 2016 ). Alternatively, age might represent temporal processing deficits not captured by the temporal processing predictors employed here.…”
Section: Discussionmentioning
confidence: 99%
“…The aspects in question are uncertain. Perhaps, age represents cognitive decline different from working memory capacity, such as processing speed ( Salthouse, 1996 ) or attention ( Craik & Byrd, 1982 ), both of which might affect performance in demanding speech-in-noise situations (e.g., Cahana-Amitay et al., 2016 ; Oberfeld & Klöckner-Nowotny, 2016 ). Alternatively, age might represent temporal processing deficits not captured by the temporal processing predictors employed here.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have identified an influence of attentional abilities on speech-in-noise recognition in young normal-hearing (Oberfeld and Klöckner-Nowotny, 2016 , age range: 18–30 years) and in elderly participants. In the elderly, participants with a wide range of hearing thresholds (Cahana-Amitay et al, 2016 , age-range: 55–84 years) as well as groups with mild hearing loss without aiding (Heinrich et al, 2015 , age range: 50–74 years) or mild-to-moderate hearing-impaired hearing aid wearers were examined (Heinrich et al, 2016 , age range: 50–74 years). The results indicate that the relationship between attention and speech recognition is to this extent independent of age and hearing loss.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, these skills include the general capacity of WM, controlled fluency (the ability to process stimuli rapidly under concentration demands), 22 and inhibition-concentration (the ability to concentrate on information relevant to the task while suppressing prepotent or automatic responses not relevant to the task). 23 In particular, support for the role of inhibition-concentration in speech recognition comes from studies demonstrating that a reduction in older adults' ability to ignore task-irrelevant information is an important contributor to their difficulty recognizing words in noise. 4,24,25 Inhibitory processes may also facilitate the identification of correct lexical items and inhibit incorrect responses.…”
Section: Introductionmentioning
confidence: 99%